1983
DOI: 10.1007/bf00015039
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal patchiness in zooplankton populations in two Ontario kettle lakes

Abstract: Horizontal distributions of zooplankton were investigated in two kettle lakes in southern Ontario . In Tory Lake a set of random samples at I m depth showed that Skistodiaptomus oregonensis and copepod nauplii were overdispersed (patchy) . In Lake St . George a 20 point grid sampled at each of 0 .5, 2, 4, and 6 m showed that Polyarthra spp ., Keratella cochlearis, Asplanchna spp ., Daphnia galeata mendotae, Bosmina longirostris, Eubosmina coregoni and copepod nauplii were all patchy in terms of both vertical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 54 publications
3
62
1
Order By: Relevance
“…Jeppesen et al, 1990). Moreover, it has become increasing clear that aquatic environments are not as homogenous as previously assumed, but that many zooplankton and phytoplankton populations show a high degree of patchiness in their distributions (George & Edwards, 1976;Harris, 1980), with, as was reported by Malone & McQueen (1983) differences of upto a factor three in chlorophyll content within a distance of a few meters. This implies that a slight horizontal or vertical movement of the daphnids could lead to different feeding conditions rather rapidly.…”
Section: Discussionmentioning
confidence: 87%
“…Jeppesen et al, 1990). Moreover, it has become increasing clear that aquatic environments are not as homogenous as previously assumed, but that many zooplankton and phytoplankton populations show a high degree of patchiness in their distributions (George & Edwards, 1976;Harris, 1980), with, as was reported by Malone & McQueen (1983) differences of upto a factor three in chlorophyll content within a distance of a few meters. This implies that a slight horizontal or vertical movement of the daphnids could lead to different feeding conditions rather rapidly.…”
Section: Discussionmentioning
confidence: 87%
“…Our understanding of zooplankton populations has been impeded because zooplankton are known to be extremely patchy, and the patterns of distribution have been difficult to discern with conventional sampling methodology. Patchy zooplankton distributions have been found wherever people looked for them (Whiteside 1974;Malone andMcQueen 1983), andDowning (1991) concluded that zooplankton, although transported passively by water movements, are as spatially aggregated as most other groups of aquatic organisms.…”
mentioning
confidence: 99%
“…Previous studies have documented zooplankton-phytoplankton interactions through correlation analysis, but the trophic consequences of such interactions were not quantified (Mackas and Boyd 1979;Star and Mullin 1981;Malone and McQueen 1983). Studies have also shown that zooplankton spatial patterns can differ depending on body size (Martin and Srokosz 2002), especially if these patterns are wind-driven (Blukacz et al 2009).…”
Section: Discussionmentioning
confidence: 99%